The Use of CIRC Strategy on Students’ Reading Comprehension Skill - imam nur aziz (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Reading is the most and useful skill for people. It is an activity that can update any information or knowledge. This research aims to know the effect of CIRC strategy on students' reading comprehension skills in the description text. This study used a quasi-experimental in which design involves two groups, namely the experimental group and the control group. The research was conducted in the experimental class consists of 20 students, and the control class consists of 20 students. The results show that The minimum score of pre-tests in the experiment class was 44, and the maximum was 84. While the minimum score of pre-tests in the control class was 44and, the ceiling was 78. On the other side, the mean of each group was different. The mean score of the pre-test experiment was 68,00, and the mean score of pre-test control was 61,50, and The minimum score of post-tests in the experiment class was 80, and the maximum was 92. While the minimum score of post-tests in the control class was 68, and the maximum was 84. On the other side, the mean of each group was different. The mean score of the post-test experiment was 85,00, and the mean score of post-test control was 75,30.